A systematic review of the effect of telephone, internet or combined support for carers of people living with Alzheimer's, vascular or mixed dementia in the community. (September 2016) - Jackson, David; Roberts, Gail; Wu, Min Lin; Ford, Rosemary; Doyle, Colleen
Highlights: Dementia is a major public health challenge, and family carers can find face to face education or counselling programs challenging to access. Few studies have considered the effectiveness of telephone, internet or combined delivery in supporting family carers of people living with dementia. This review evaluated the effectiveness of interventions consisting of supportive, psychotherapeutic, educational or combinations delivered by telephone, internet or combinations. Combined interventions delivered in combined formats appeared to deliver the most positive outcomes but the small number of studies meant that conclusions should be interpreted cautiously. Few studies considered the specific needs of carers of people with vascular dementia or mixed dementia. Abstract: Background: The objective of this review was to assess the effectiveness of interventions delivered by telephone, internet or combined formats to support carers of community dwelling people living with Alzheimer's Disease, vascular dementia or mixed dementia. Method: English language literature published up to 2016 was searched. The initial search included: MEDLINE, Cumulative Index to Nursing and Allied Health (CINAHL), and PsycINFO. A second search was conducted using Medical Subject Headings (MeSH) and keywords for eight databases. The review included randomised controlled trials, non-randomised controlled trials, quasi-experimental and pre-post studies from published and grey literature. Studies selected for retrieval were assessed by three independent reviewers for methodological validity prior to inclusion in the review using standardised critical appraisal instruments. Results: Twenty-two studies were included in the review of which 13 were studies of telephone-delivered interventions, five were internet-delivered interventions and four were delivered in a combination of telephone and internet formats. In this review the successful outcomes from the combined telephone and internet delivery exceeded that of telephone alone and internet alone. Very few studies addressed programs for specific types of dementia. Conclusion: When considering the ratio of number of studies to successful outcomes, combined telephone and internet delivery of multicomponent interventions demonstrated relatively more positive outcomes in reducing depression, burden and increasing self-efficacy than telephone alone or internet alone. Further studies are necessary to evaluate the effectiveness of interventions targeted at specific types of dementia and to understand which components of interventions are most effective.